High-stability glue for polishing process

By adding rosin asphalt stabilizer and antioxidant and antibacterial complex to the glue, the influence of ultraviolet rays on the glue performance is solved, the stability and UV resistance of the glue are improved, and higher adhesion and durability are achieved.

CN120272126AInactive Publication Date: 2025-07-08JIANGSU YUDI OPTICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510640681.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-07-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The impact of ultraviolet rays on glue performance during production leads to a decline in product quality, and it is difficult for the existing technology to effectively improve the stability and UV resistance of glue.

Method used

Antioxidants are prepared by combining rosin and asphalt, combined with lignin, pretreated carboxymethylcellulose and antibacterial complex, and antibacterial complexes are prepared by polystyrene and D-limonene, forming a synergistically improving the stability of the glue system.

Benefits of technology

It improves the adhesion, cohesion and UV resistance of the glue, reduces moisture penetration, enhances the stability and durability of the glue, inhibits microbial erosion, and improves overall stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005408106510000081
    Figure BDA0005408106510000081
  • Figure BDA0005408106510000091
    Figure BDA0005408106510000091
Patent Text Reader

Abstract

The invention relates to high-stability glue for a polishing process, the glue can be used in the polishing process, and the high-stability glue comprises the following components in parts by mass: 10-60 parts of isobornyl methacrylate, 50-60 parts of ethyl acrylate, 18-22 parts of ethyl acetate, 24-28 parts of pentaerythritol, 18-22 parts of isocyanate, 12-14 parts of a stabilizer, 8-10 parts of a plasticizer and 13-15 parts of an antioxidant. The stabilizer comprises rosin and asphalt. The preparation method has the effect of improving the stability of the prepared glue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of aperture production, and in particular to a highly stable glue for polishing process. Background Art

[0002] OCA optical glue is a colorless and transparent special adhesive, mainly used for bonding optical elements such as glass, plastics, etc. with other components to achieve the assembly and fixation of optical systems. OCA optical glue is used for bonding between lenses, which can ensure the precise position and angle of the lenses, reduce light scattering and distortion, and thus ensure that the lens has good resolution, contrast and color restoration at large apertures. For example, in the large-aperture fixed-focus lenses of some high-end cameras, OCA optical glue can accurately bond multiple lenses, making the lens present delicate and clear image quality when shooting at large apertures.

[0003] In the production work, ultraviolet light is one of the factors affecting the performance of the glue. During the equipment production process, ultraviolet disinfection is usually required. Under long-term ultraviolet irradiation, it is very easy to cause the performance of the glue to decline, thus affecting the quality of product production. Summary of the Invention

[0004] In order to solve the above problems, the present application provides a highly stable glue for polishing process.

[0005] The highly stable glue for polishing process provided by the present application adopts the following technical solutions: A highly stable glue for polishing process, comprising the following components by mass fraction: Isobornyl methacrylate 10 - 60 parts Ethyl acrylate 50 - 60 parts Ethyl acetate 18 - 22 parts Pentaerythritol 24 - 28 parts Isocyanate 18 - 22 parts Stabilizer 12 - 14 parts Plasticizer 8 - 10 parts Antioxidant 13 - 15 parts; The stabilizer includes rosin and tar.

[0006] By adopting the above technical solution, a stabilizer composed of a compound of rosin and tar is added to the system, which can further improve the overall stability of the glue. Rosin has good viscosity, which can improve the adhesion force between the glue and the surface of the adherend, so that the glue can adhere to the surface of the object more stably. At the same time, it can improve the internal cohesion of the glue, making it difficult for the glue to be damaged under the action of external forces, so as to further improve the peel strength of the system. At the same time, rosin has good hydrophobic properties, which can reduce the penetration and erosion of water on the glue, so as to improve the overall stability of the glue; white oil has good anti-ultraviolet properties, which can form a shielding layer to absorb and scatter light, thus reducing the influence of ultraviolet rays on the stability of the glue, so as to improve the overall stability of the glue.

[0007] Preferably, the mass ratio between the rosin and the tar is (2.9-3.1):1.

[0008] By adopting the above technical solution, preferably, the mass ratio of rosin to tar is within the above range, which can make the rosin and the tar combine better and synergistically improve the overall stability of the glue system.

[0009] Preferably, the antioxidant includes lignin, pretreated carboxymethyl cellulose and antibacterial complex.

[0010] By adopting the above technical solution, an antioxidant is added to the system to improve the overall antioxidant performance of the glue system, thereby improving the stability of the glue system. Among them, lignin is a renewable resource in aromatic compounds and has a three-dimensional network structure. Adding it to the system can not only improve the overall anti-ultraviolet and antioxidant performance of the system, but also further combine the pretreated carboxymethyl cellulose and the antibacterial complex, thus improving the binding effect and stability of the antioxidant in the system, and further improving the overall comprehensive performance of the system; carboxymethyl cellulose has the characteristics of a hierarchical molecular structure and can form a stable network structure in the glue system to improve the stability of the glue. At the same time, carboxymethyl cellulose has a large number of hydroxyl and carboxyl groups to capture free radicals, thus improving the antioxidant performance of the glue system. By combining with the antibacterial complex, the system has good antibacterial performance, reducing the occurrence of the phenomenon of the glue being eroded by microorganisms, and further improving the overall stability of the glue.

[0011] Preferably, the pretreated carboxymethyl cellulose is prepared by the following method: Add carboxymethyl cellulose to sodium hydroxide solution, stir and then add (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride to obtain a mixed system. Heat up the mixed system and stir to react, and then wash and dry to obtain pretreated carboxymethyl cellulose.

[0012] The structure of carboxymethyl cellulose contains a large number of hydroxyl and carboxyl groups, and its surface shows electronegativity. The surface of lignin also shows electronegativity. By adopting the above technical solution, (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride is used to further treat carboxymethyl cellulose, so as to adjust the charge on the surface of carboxymethyl cellulose. (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride is converted into glycidyl trimethyl ammonium in an alkaline environment, and its epoxy group reacts with the hydroxyl group on the surface of carboxymethyl cellulose to etherify, so that carboxymethyl cellulose is cationically modified to obtain pretreated carboxymethyl cellulose, which can further combine with lignin, thus improving the overall stability of the prepared antioxidant.

[0013] Preferably, the mass concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system is 62-66 wt%.

[0014] By adopting the above technical solution, preferably, the mass concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system is within the above range, which can further improve the overall stability of the prepared pretreated carboxymethyl cellulose.

[0015] Preferably, the antibacterial complex includes polystyrene and D-limonene.

[0016] By adopting the above technical solution, polystyrene has good viscosity. Adding it to the glue system can further improve the cohesion of the glue and the adhesion to the adherend. At the same time, it has good heat resistance to improve the overall stability of the glue system. D-limonene is an environmentally friendly natural oil and a weak acid, which can inhibit the growth and reproduction of microorganisms, thus playing a good antibacterial performance. The antibacterial complex prepared by combining the two has good stability and antibacterial performance. At the same time, D-citric acid can play a synergistic antibacterial role with lignin, and functional groups such as carbon-carbon double bonds in the structure of D-limonene can react with free radicals, thus further improving the overall antibacterial and antioxidant performance of the system with lignin. At the same time, after polystyrene binds to lignin, the fluidity and thermal stability of the antioxidant as a whole can be improved, further enhancing the overall comprehensive performance of the system.

[0017] Preferably, the antibacterial complex is prepared by the following method: Dry polystyrene and mix it with D-limonene, add ethanol after stirring to obtain a mixture, heat up and stir the mixture, and obtain the antibacterial complex after cooling and crushing.

[0018] By adopting the above technical solution, through the combination of D-limonene and polystyrene and heat treatment, the prepared antibacterial composite has the characteristics of light weight and low density. The prepared system has good stability and good antibacterial performance, and can be further combined with lignin and pretreated carboxymethyl cellulose to improve the overall comprehensive performance of the system.

[0019] Preferably, the mass ratio between the polystyrene and D-limonene is 1:(2.6-2.8).

[0020] By adopting the above technical solution, preferably, when the mass ratio between the polystyrene and D-limonene is within the above range, the overall stability of the prepared antibacterial composite can be further improved.

[0021] Preferably, the antioxidant is prepared by the following method: Mix lignin with water to obtain a lignin dispersion. Add sodium hydroxide to the lignin dispersion and stir to obtain a lignin solution. Add the pretreated carboxymethyl cellulose and the antibacterial composite to the lignin solution, heat up and stir to obtain a composite. Add hydrochloric acid to the composite to adjust the pH of the system to 2-3, continue stirring, stand, wash, freeze-dry, and crush to obtain the antioxidant.

[0022] Preferably, the mass ratio between the pretreated carboxymethyl cellulose, lignin and the antibacterial composite is 1:(0.26-0.36):0.76.

[0023] By adopting the above technical solution, preferably, when the mass ratio between the lignin, the pretreated carboxymethyl cellulose and the antibacterial composite is within the above range, the overall stability of the prepared antibacterial composite can be further improved.

[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, a stabilizer prepared from rosin and tar is added to the system. Rosin has good viscosity, which can further improve the adhesion between the glue system and the surface of the adherend, thereby improving the stability of the glue. Moreover, it can enhance the internal cohesion of the glue, further improving the stability of the glue. White oil has good ultraviolet resistance and can form a shielding layer, effectively reducing the influence of ultraviolet rays on the stability of the glue. At the same time, the two can synergistically improve the overall stability of the glue, thus enhancing the durability of the glue; 2. An antioxidant is added to the glue system. The antioxidant is prepared from lignin, pretreated carboxymethyl cellulose and an antibacterial complex. Lignin is a renewable resource of aromatic compounds with a three-dimensional network structure, which further improves the stability of the prepared antioxidant. Carboxymethyl cellulose has the structural characteristics of hierarchical molecules, can form a network structure in the glue system, and can capture free radicals, thus synergistically enhancing the overall antioxidant performance of the system with lignin, reducing the occurrence of the phenomenon that the glue is eroded by microorganisms, and further improving the overall stability of the glue; 3. An antibacterial complex is prepared by combining polystyrene and D-limonene. Polystyrene has good adhesiveness. Adding it to the glue system can further improve the bonding performance between the glue and the adherend. At the same time, due to the good antibacterial performance and free radical scavenging effect of D-limonene, the glue system can have good antibacterial and antioxidant properties, thus further improving the durability of the glue. Detailed implementation mode

[0025] The following further elaborates on this application with reference to examples: Raw material description: All raw materials in the examples can be obtained commercially; among them, the plasticizer is dioctyl phthalate (CAS No.: 117-84-0).

[0026] Example 1 Prepare an antibacterial complex: Wash 5.56 g of polystyrene (CAS No.: 9003-53-6) with deionized water and dry it in an oven at 40 °C for 5 h. Then mix 14.44 g of D-limonene (CAS No.: 7705-14-8) with the dried polystyrene, add 50 g of ethanol after stirring, obtain a mixture, heat the mixture to 190 °C, keep the temperature and continue stirring for 5 h, then naturally cool to 25 °C, and break it to obtain an antibacterial complex.

[0027] Prepare pretreated carboxymethyl cellulose: Dry carboxymethyl cellulose (CAS No.: 9000-11-7) in an oven at 50 °C for 2 h to remove moisture. Then add the dried carboxymethyl cellulose to a sodium hydroxide solution with a mass fraction of 30 wt%, stir for 1 h, and then add (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride (CAS No.: 3327-22-8) to obtain a mixed system. The mass fraction of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system is 62 wt%. Heat the mixed system to 65 °C, stir and react for 10 h, then wash with deionized water and dry at 40 °C for 3 h to obtain pretreated carboxymethyl cellulose.

[0028] Prepare an antioxidant: Mix 2.57 g of lignin (CAS No.: 8068-05-1) with deionized water to obtain a lignin dispersion. Add 50 g of sodium hydroxide to the lignin dispersion and stir for 20 min to obtain a lignin solution. Add 9.9 g of pretreated carboxymethyl cellulose and 7.53 g of antibacterial complex to the lignin solution, heat up to 90 °C, and stir for 10 min to obtain a complex. Add hydrochloric acid to the complex to adjust the pH of the system to 2.5, continue stirring for 30 min, then let it stand for 30 min. Finally, wash with deionized water and freeze-dry at -20 °C for 12 h. After crushing, an antioxidant is obtained.

[0029] Prepare a stabilizer: Mix 14.87 g of rosin (CAS No.: 8050-09-7) and 15.12 g of tar (CAS No.: 8013-86-3), and stir for 40 min to obtain a stabilizer.

[0030] Prepare a highly stable glue for the polishing process: Heat 40 g of isobornyl methacrylate (CAS No.: 7534-94-3), 50 g of ethyl acrylate (CAS No.: 140-88-5), and 18 g of ethyl acetate (CAS No.: 141-78-6) to 80 °C, stir at a speed of 500 rpm for 20 min, then add 24 g of pentaerythritol (CAS No.: 115-77-5) and 18 g of isocyanate (CAS No.: 75-13-8), heat up to 120 °C, and stir at a speed of 650 rpm for 30 min to obtain a preform. Add 12 g of stabilizer, 8 g of plasticizer, and 13 g of antioxidant to the preform, continue to stir at a temperature of 120 °C for 30 min, then cool to 60 °C and continue stirring for 1 h. After vacuum degassing in a degassing machine, a highly stable glue for the polishing process is obtained.

[0031] Example 2 Prepare an antibacterial complex: Wash 5.26 g of polystyrene with deionized water and dry it in an oven at 40 °C for 5 h. Then mix 14.74 g of D-limonene with the dried polystyrene, stir and add 50 g of ethanol to obtain a mixture. Heat the mixture to 190 °C, keep the temperature and continue stirring for 5 h, then naturally cool to 25 °C. After crushing, an antibacterial complex is obtained.

[0032] Prepare pretreated carboxymethyl cellulose: Carboxymethyl cellulose was dried in an oven at 50 °C for 2 h to remove moisture. Then, the dried carboxymethyl cellulose was added to a sodium hydroxide solution with a mass fraction of 30 wt%, stirred for 1 h, and then (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride was added to obtain a mixed system. The mass fraction of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system was 66 wt%. The mixed system was heated to 65 °C and stirred and reacted for 10 h. Then, it was washed with deionized water and dried at 40 °C for 3 h to obtain pretreated carboxymethyl cellulose.

[0033] Preparation of antioxidant: 3.4 g of lignin was mixed with deionized water to obtain a lignin dispersion. 50 g of sodium hydroxide was added to the lignin dispersion and stirred for 20 min to obtain a lignin solution. 9.43 g of pretreated carboxymethyl cellulose and 7.17 g of antibacterial complex were added to the lignin solution, heated to 90 °C, and stirred for 10 min to obtain a complex. Hydrochloric acid was added to the complex to adjust the pH of the system to 2.5, and stirring was continued for 30 min. Then, it was allowed to stand for 30 min. Finally, it was washed with deionized water and freeze-dried at -20 °C for 12 h, and then crushed to obtain the antioxidant.

[0034] Preparation of stabilizer: 15.12 g of rosin was mixed with 4.88 g of tar and stirred for 40 min to obtain the stabilizer.

[0035] Preparation of highly stable glue for polishing process: 60 g of isobornyl methacrylate, 60 g of ethyl acrylate, and 22 g of ethyl acetate were heated to 80 °C and stirred at a speed of 500 rpm for 20 min. Then, 28 g of pentaerythritol and 22 g of isocyanate were added, and the temperature was raised to 120 °C and stirred at a speed of 650 rpm for 30 min to obtain a preform. 14 g of stabilizer, 10 g of plasticizer, and 15 g of antioxidant were added to the preform, and stirring was continued at 120 °C for 30 min. Then, it was cooled to 60 °C and stirred for 1 h. After vacuum degassing in a degassing machine, the highly stable glue for polishing process was obtained.

[0036] Example 3 Preparation of antibacterial complex: 5.41 g of polystyrene was washed with deionized water and dried in an oven at 40 °C for 5 h. Then, 14.59 g of D-limonene was mixed with the dried polystyrene, stirred, and 50 g of ethanol was added to obtain a mixture. The mixture was heated to 190 °C, the temperature was maintained, and stirring was continued for 5 h. Then, it was naturally cooled to 25 °C and crushed to obtain the antibacterial complex.

[0037] Preparation of pretreated carboxymethyl cellulose: Carboxymethyl cellulose was dried in an oven at 50 °C for 2 h to remove moisture. Then, the dried carboxymethyl cellulose was added to a sodium hydroxide solution with a mass fraction of 30 wt%, and stirred for 1 h. Then, (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride was added to obtain a mixed system. The mass fraction of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system was 64 wt%. The mixed system was heated to 65 °C and stirred for 10 h, then washed with deionized water and dried at 40 °C for 3 h to obtain pretreated carboxymethyl cellulose.

[0038] Preparation of antioxidant: 3 g of lignin was mixed with deionized water to obtain a lignin dispersion. 50 g of sodium hydroxide was added to the lignin dispersion and stirred for 20 min to obtain a lignin solution. 9.66 g of pretreated carboxymethyl cellulose and 7.34 g of antibacterial complex were added to the lignin solution, heated to 90 °C, and stirred for 10 min to obtain a complex. Hydrochloric acid was added to the complex to adjust the pH of the system to 2.5, and stirring was continued for 30 min. Then, it was allowed to stand for 30 min. Finally, it was washed with deionized water and freeze-dried at -20 °C for 12 h, and crushed to obtain the antioxidant.

[0039] Preparation of stabilizer: 15 g of rosin was mixed with 5 g of pitch and stirred for 40 min to obtain the stabilizer.

[0040] Preparation of high-stability glue for polishing process: 50 g of isobornyl methacrylate, 55 g of ethyl acrylate, and 20 g of ethyl acetate were heated to 80 °C and stirred at a speed of 500 rpm for 20 min. Then, 26 g of pentaerythritol and 20 g of isocyanate were added, and the temperature was raised to 120 °C and stirred at a speed of 650 rpm for 30 min to obtain a preform. 13 g of stabilizer, 9 g of plasticizer, and 13 g of antioxidant were added to the preform, and stirring was continued at 120 °C for 30 min. Then, it was cooled to 60 °C and stirred for 1 h. After vacuum degassing in a degassing machine, the high-stability glue for polishing process was obtained.

[0041] Example 4 Example 4 was based on Example 3. In Example 4, when preparing the stabilizer, 14.29 g of rosin and 5.71 g of pitch were used.

[0042] Example 5 Example 5 was based on Example 3. In Example 5, when preparing the stabilizer, 15.56 g of rosin and 4.44 g of pitch were used.

[0043] Example 6 Example 6 Based on Example 3, when preparing the antibacterial composite in Example 6, 6.25 g of polystyrene and 13.75 g of D-limonene were used.

[0044] Example 7 Example 7 Based on Example 3, when preparing the antibacterial composite in Example 7, 4.76 g of polystyrene and 15.24 g of D-limonene were used.

[0045] Example 8 Example 8 Based on Example 3, when preparing the pretreated carboxymethyl cellulose in Example 8, the mass concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system was 58 wt%. Example 9 Example 9 Based on Example 3, when preparing the pretreated carboxymethyl cellulose in Example 9, the mass concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system was 70 wt%.

[0046] Example 10 Example 10 Based on Example 3, when preparing the antioxidant in Example 10, 2.04 g of lignin, 10.2 g of pretreated carboxymethyl cellulose, and 7.76 g of antibacterial composite were used.

[0047] Example 11 Example 11 Based on Example 3, when preparing the antioxidant in Example 11, 3.78 g of lignin, 9.22 g of pretreated carboxymethyl cellulose, and 7 g of antibacterial composite were used.

[0048] Example 12 Example 12 Based on Example 3, when preparing the antioxidant in Example 3, the pretreated carboxymethyl cellulose was replaced with untreated ordinary carboxymethyl cellulose.

[0049] Example 13 Example 13 Based on Example 3, when preparing the antioxidant in Example 13, the antibacterial composite was replaced with D-limonene.

[0050] Example 14 Example 14 Based on Example 3, when preparing the antioxidant in Example 14, no antibacterial composite was added.

[0051] Comparative Example 1 Comparative Example 1 Based on Example 3, no rosin was added to the stabilizer in Comparative Example 1.

[0052] Comparative Example 2 Comparative Example 2 Based on Example 3, no tar was added to the stabilizer in Comparative Example 2.

[0053] Performance detection test For the specimens of Examples 1-14 and Comparative Examples 1-2, the following performance tests were carried out: (1) Peel strength test Taking "GB / T 2792-2014 180" as the detection standard, the peel strength of the specimens with a thickness of 100μm was tested using a KJ-065B peel force testing machine. Each specimen was tested three times, and the average value was taken, and the test results were filled in Table 1.

[0054] (2) Thermal aging performance test The specimens were aged in an environment of 50°C and a relative humidity of 50% for 48h, and then the peel strength of the specimens with a thickness of 100μm after thermal aging was tested. Each specimen was tested 3 times, and the average value was taken, and the test results were filled in Table 1.

[0055] (3) UV aging performance test Taking "GB / T 16422.3-2014" as a reference, the specimens were subjected to UV aging, and then the peel strength of the specimens with a thickness of 100μm after UV aging was tested. Each specimen was tested 3 times, and the average value was taken, and the test results were filled in Table 1.

[0056] (2) Antibacterial performance test Taking "GB / T 31402-2015" as a reference, the antibacterial performance of the specimens was tested. Each specimen was tested 3 times, and the average value was taken, and the test results were filled in Table 1.

[0057] Table 1 Performance test results of Examples 1-14 and Comparative Examples 1-2 Combined with Table 1, it can be seen that the peel strength of Examples 1-3 is all 2.84 / Kg / 2.54cm or above, indicating that the glue prepared in this application has good stability. The peel strength of Examples 1-3 after thermal aging is all 2.22Kg / 2.54cm or above, indicating that the glue prepared in this application has good thermal stability. The peel strength of Examples 1-3 after UV aging is all 2.36Kg / 2.54cm or above, indicating that the glue prepared in this application has good UV resistance. The antibacterial rate of Escherichia coli in Examples 1-3 is all 98.2% or above, and the antibacterial rate of Staphylococcus aureus is all 97.5% or above, indicating that the glue prepared in this application has good antibacterial performance.

[0058] In Example 4 and Example 5 during the preparation of the stabilizer, the mass ratio between rosin and tar is not within the scope defined in this application. When the addition amount of rosin is too small, due to the viscosity of rosin, the viscosity of the glue will be too high, and it will affect the dispersion uniformity of other substances in the system, affecting the overall stability of the system. When the content of rosin is too small, it is difficult to further improve the bonding performance of the glue system, resulting in a decrease in the viscosity of the glue and a decrease in stability. At the same time, rosin has an antioxidant effect, and the decrease in the rosin content will also affect the antioxidant performance of the system. Therefore, the performance of Example 4 and Example 5 has both decreased.

[0059] In Example 6 and Example 7 during the preparation of the antibacterial complex, the mass ratio between polystyrene and D-limonene is not within the scope defined in this application. When the content of D-limonene is too small, it is difficult to make sufficient contact with polystyrene, resulting in a decrease in the solubility of the antibacterial complex and a decrease in the stability of the prepared antibacterial complex, affecting the overall stability of the system; when the content of D-limonene is too large, there will be too much organic residue in the prepared antibacterial complex, which will also affect the overall stability of the system. Therefore, the performance of Example 6 and Example 7 has both decreased.

[0060] In Example 8 and Example 9 during the preparation of the pretreated carboxymethyl cellulose, the mass concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride in the mixed system is not within the scope defined in this application. When the mass concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride is too small, it is difficult to further adjust the charge on the surface of carboxymethyl cellulose, and the binding performance between the subsequent carboxymethyl cellulose and lignin decreases, affecting the overall stability of the system. When the concentration of (3-chloro-2-hydroxypropyl) trimethyl ammonium chloride is too large, the original molecular structure and crystallization performance of carboxymethyl cellulose are damaged, resulting in a decrease in the thermal stability of the modified product, and thus the stability of the prepared pretreated carboxymethyl cellulose decreases. Therefore, the performance of Example 8 and Example 9 has both decreased.

[0061] In Example 10 and Example 11 during the preparation of the antioxidant, the mass ratio among lignin, pretreated carboxymethyl cellulose and the antibacterial complex is not within the scope defined in this application. When the content of lignin is too small currently, the effective components of the overall antioxidant and anti-ultraviolet performance of the system decrease, thus affecting the overall stability of the system; when the content of lignin is too large, the original molecular structure of carboxymethyl cellulose is damaged, resulting in a decrease in the overall stability of the system. Therefore, the performance of Example 10 and Example 11 has both decreased.

[0062] Example 12 When preparing the antioxidant, the pretreated carboxymethyl cellulose was replaced with untreated ordinary carboxymethyl cellulose. It is difficult to modify the surface charge of ordinary carboxymethyl cellulose, and its binding performance with lignin is poor. It is difficult to improve the stability of the prepared antioxidant, which affects the overall performance of the system. Therefore, the performance of Example 12 decreased.

[0063] In Example 13, the antibacterial complex was replaced with D-limonene. Without adding the antibacterial complex of polystyrene, the viscosity and stability decreased, and the binding performance between each component decreased. Therefore, the performance of Example 13 decreased.

[0064] In Example 14, the antioxidant did not add the antibacterial complex. The antibacterial active ingredient and the heat-stable active ingredient of the antioxidant both decreased. It was difficult to play a role in synergistically improving the antibacterial performance and heat-stable performance of the system. Moreover, without the addition of polystyrene, it was difficult to further improve the stability between components. Therefore, the performance of Example 14 all decreased.

[0065] In Comparative Example 1, rosin was not added to the stabilizer, and in Comparative Example 2, tar was not added to the stabilizer. Only a single component was used as the stabilizer, and it was difficult to synergistically improve the overall stability of the system. Therefore, the performance of both Comparative Example 1 and Comparative Example 2 decreased.

[0066] This specific embodiment is only an interpretation of the present application and does not limit the present application. Through the above description, relevant staff can make various changes and modifications completely within the scope of the technical idea of this application without deviation. The technical scope of this application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high-stability glue for a polishing process, characterized in that: Components including the following quality scores: 10 - 60 parts of isobornyl methacrylate 50 - 60 parts of ethyl acrylate 18 - 22 parts of ethyl acetate 24 - 28 parts of pentaerythritol 18 - 22 parts of isocyanate 12 - 14 parts of stabilizer 8 - 10 parts of plasticizer 13 - 15 parts of antioxidant; The stabilizer includes rosin and tar.

2. The highly stable glue for a polishing process according to claim 1, wherein: The mass ratio between the rosin and the tar is (2.9 - 3.1):

1.

3. The high-stability glue for a polishing process according to claim 1, characterized in that: The antioxidant includes lignin, pretreated carboxymethyl cellulose, and antibacterial complex.

4. The high-stability glue for a polishing process according to claim 3, characterized in that: The pretreated carboxymethyl cellulose is prepared by the following method: Add carboxymethyl cellulose into sodium hydroxide solution, stir and then add (3 - chloro - 2 - hydroxypropyl) trimethyl ammonium chloride to obtain a mixed system. Heat up the mixed system and stir for reaction, then wash and dry to obtain pretreated carboxymethyl cellulose.

5. The high-stability glue for a polishing process according to claim 4, characterized in that: The mass concentration of (3 - chloro - 2 - hydroxypropyl) trimethyl ammonium chloride in the mixed system is 62 - 66 wt%.

6. The highly stable glue for a polishing process according to claim 3, wherein: The antibacterial complex includes polystyrene and D - limonene.

7. The highly stable glue for a polishing process according to claim 6, wherein: The antibacterial complex is prepared by the following method: Dry polystyrene and mix it with D - limonene, stir and then add ethanol to obtain a mixture. Heat up the mixture and stir, cool and crush to obtain the antibacterial complex.

8. The high-stability glue for a polishing process according to claim 7, characterized in that: The mass ratio between the polystyrene and D - limonene is 1:(2.6 - 2.8).

9. The high-stability glue for a polishing process according to claim 3, characterized in that: The antioxidant is prepared by the following method: Mix lignin with water to obtain a lignin dispersion. Add sodium hydroxide to the lignin dispersion and stir to obtain a lignin solution. Add the pretreated carboxymethyl cellulose and the antibacterial complex to the lignin solution, heat up and stir to obtain a complex. Add hydrochloric acid to the complex to adjust the pH of the system to 2 - 3, continue to stir, stand still and then wash, freeze - dry, and crush to obtain the antioxidant.

10. A high-stability glue for a polishing process according to claim 9, characterized in that: The mass ratio among the pretreated carboxymethyl cellulose, lignin, and antibacterial complex is 1:(0.26 - 0.36):0.76.

Citation Information

Patent Citations

  • Antibacterial, uvioresistant, heat-resisting and anticorrosion composite material

    CN106366876A

  • Special flame-retardant adhesive for paper carton and preparation method of special flame-retardant adhesive

    CN109486427A

  • Stable OCA (Optical Clear Adhesive)

    CN115785827A

  • Preparation method of high-hardness antibacterial polystyrene engineering plastic

    CN116253924A

  • Preparation method and application of cellulose-based toughening and reinforcing material for UV photocuring

    CN118812731A